Metabolic load comparison between the quarters of a game in elite male basketball players using sport metabolomics - Khoramipour, K.; Gaeini, A. A.; Shirzad, E.; Gilany, K.; Chashniam, S.; Sandbakk, Ø. (European Journal of Sport Science, 2021)
Purpose: A basketball match is characterized as highly intermittent, thereby relying extensively on both aerobic and anaerobic metabolic pathways with four 10-min quarters. Here, we aimed to compare the metabolic fluctuations between the quarters of high-level basketball games using metabolomics analyses.